Pemanfaatan Google Formulir Pada ujian Akhir Madrasah Di Madrasah Ibtidaiyah Al Hidayah Trowulan Mojokerto - Marifah, Nurul (Inovasi: Jurnal Diklat Keagamaan, 2020)
The purpose of this study was to obtain information about the procedure of using the Google application form as well as the responses of educators and students to their use. This study uses descriptive analytical methods with data collection techniques such as questionnaires and documentation studies. The subjects in this study were educators and students in the Ibtidaiyah Al Hidayah Domas Trowulan Mojokerto Madrasah. The results obtained are the procedure of using Google Form is the process of planning, the process of making, the process of distributing links and the socialization of instructions for use. Educator response data shows that Google Form can be used as an alternative for making evaluations. This is evidenced by the results that 100% of teachers as participants have an interest in making evaluations through Google Forms. The reason for the interest has 4 references, namely, 66% ease, 77% speed, 77% practicality, and 88% efficiency. And students' interest in using Google Form in Ujian Akhir Madrasah is 74%.